From Grassroots Adult Literacy to Navigating Academia: An Autoethnography - Madevi Ramdeholl (Adult Education Research Conference, 2010)
This study chronicled the first year of a grassroots adult literacy practitioner into the world of academia. This scholar practitioner reflects on her transition into this culture and the implications for other new scholars of color.